Significance of determination of tacrolimus intraindividual variability and pharmacogenetic markers in kidney transplant recipients - Stefanović, Nikola (Archives of Pharmacy, 2022)
In the last three decades, a significant success was achieved in short-term outcomes after kidney transplantation, but it has not been followed with the same progress in long-term post-transplantation period. Long-term graft survival depends on genetic, immunological factors and patient-individualized immunosuppressive pharmacotherapy. Tacrolimus (Tac) is the backbone of the most immunosuppressive protocols after kidney transplantation nowadays and it is likely to be in a following decade. However, narrow therapeutic index and marked pharmacokinetic inter- and intra-individual variability complicate its clinical application. Therefore, therapeutic monitoring of Tac is necessary, but not sufficient to prevent graft rejection and/or the occurrence of adverse effects (renal dysfunction, hypertension, etc.). Cytochrome P450 (CYP) 3A5 6986A>G gene polymorphism is assumed to be a major determinant of interindividual pharmacokinetic variability of Tac. The carriers of functionally isoenzyme (expressers) require higher daily doses of Tac and have lower trough concentration in whole blood/daily dose ratio (C0/D) of Tac compared to non-expressers (1). Given the inconsistency of the results regarding CYP3A5 effect on long-term post-transplantation outcomes, the investigation of new pharmacogenetic biomarkers could be of great importance. A growing number of studies have been focused on the association of interindividual and/or intraindividual variability of Tac exposure in the first post-transplantation year with adverse outcomes in later periods (e.g. late acute rejection, chronic dysfunction, rejection and graft loss) (2). The introduction of CYP3A5 genotyping into clinical practice, simultaneously with the assessment of Tac C0/D and intraindividual variability may categorize patients towards risk of graft function deterioration in long-term post-transplantation period.